1977
DOI: 10.1126/science.860131
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Emissions from Geothermal Power Plants

Abstract: Geothermal steam used for power production contains significant quantities of volatile mercury. Much of this mercury escapes to the atmosphere as elemental mercury vapor in cooling tower exhausts. Mercury emissions from geothermal power plants, on a per megawatt (electric) basis, are comparable to releases from coal-fired power plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This can constitute a pollution problem but can also provide an interesting possibility for prospecting for geothermal energy [Varekamp and Buseck, 1983]. Previous studies with mercury point monitors at the Geysers geothermal plant in California and at the Cerro Prieto plant in Mexico reveiled high concentrations of atomic mercury in the cooling tower exhaust air [Robertson et al, 1977]. In independent measurements at the Geysers geothermal plant a multi-pass atomic absorption spectrometer sensitive only to atomic mercUJY was used Vepsen, 1973].…”
Section: Introductionmentioning
confidence: 99%
“…This can constitute a pollution problem but can also provide an interesting possibility for prospecting for geothermal energy [Varekamp and Buseck, 1983]. Previous studies with mercury point monitors at the Geysers geothermal plant in California and at the Cerro Prieto plant in Mexico reveiled high concentrations of atomic mercury in the cooling tower exhaust air [Robertson et al, 1977]. In independent measurements at the Geysers geothermal plant a multi-pass atomic absorption spectrometer sensitive only to atomic mercUJY was used Vepsen, 1973].…”
Section: Introductionmentioning
confidence: 99%
“…Adding acid and allowing the samples to stand for several hours converted some of the non-reducible Hg into reducible form as would be expected from the slow acid dissolution of HgS. Robertson et al (1977) in their studies at The Geysers and Cerro Prieto reported that Hg in the steam condensate did not appear to be Hg° but was present in some colloidal form, possibly as sulphide or ammonia complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Hg in geothermal fluids partitions preferentially into the vapour phase on boiling and Weissberg (1975) noted the high steam/water distribution ratio of Hg in fluids at various geothermal fields around the world. Crecelius et al (1976) reported that elemental Hg (Hg°) is the dominant form of Hg in geothermal steam and Robertson et al (1977), in their investigations of the Hg emissions from the geothermal power stations at The Geysers (a dry steam system with no liquid water) and Cerro Prieto, found that Hg in the steam entering the stations was predominantly in the vapour state. The dominant vapour form in the steam was Hg° but in the condensed steam Hg was primarily dissolved and did not appear to be Hg°.…”
Section: Introductionmentioning
confidence: 99%
“…At the Cerro Prieto field in Mexico, hydrothermal fluids ~4th over 2 wt% C1 drculate below the sur~hce at around 270 °C (see Ellis, 1979). At the wellheads, the fluid is a mixture of 70% brine with 0.05 ppb Hg and 30% steam with 8 ppb Hg (Robertson et al, 1977). At the Geysers field in western California, hot steam with only trace chlorine emanates from vents with 0.3 ppb to 18 ppb Hg (Robertson et al, t977;Weissberg and Rohde, 1978).…”
Section: Mercury Transportmentioning
confidence: 97%